Metode Sistem Pengendalian Internal melalui Audit Berbasis Risiko (ABR) pada Inspektorat Provinsi Nusa Tenggara Timur (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to determine how the implementation of the Internal Control System and the implementation of Internal-Based Audits at the Inspectorate of East Nusa Tenggara Province. This study focuses on the assessment of the components of the Internal Control System and the implementation of Risk-Based Audits at the Inspectorate of East Nusa Tenggara Province. The research method used in this study is descriptive qualitative, data collection techniques used are observation, interviews, and documentation. Several informants interviewed include Auditors and Supervisors of Regional Government Affairs Organizer. The results of this study indicate that the Inspectorate of East Nusa Tenggara Province has implemented several components in the Internal Control System and also the implementation of Risk-Based Audits.